Effects of time of introduction and level of soybean meal on performance of segregated early-weaned pigs - P R O'Quinn; J R Bergstrom; J A Loughmiller; K Hongtrackul; R E Musser; C A Civis; C J Maxwell; Jim L Nelssen; Michael D Tokach; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1997)
A growth trial was conducted utilizing segregated early weaned (SEW) pigs to evaluate the effects of time of introduction and level of soybean meal on growth performance. Few differences were observed in growth performance indicating that including up to 40% soybean meal in the diet will not adversely affect growth of high-health status, SEW-reared pigs.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; SEW pigs; Soybean meal; Growth performance